Timing of peptide receptor radiotargeted therapy in relation to cardiac valve surgery for carcinoid heart disease in patients with neuroendocrine metastases and cardiac syndrome. A single-centre study from a centre of excellence. Issue 6 (June 2020) - Davis, Laura May; Nicou, N; Martin, Wendy; Corcoran, Ben; Mulholland, Nicola; Srirajaskanthan, R; Ramage, J; Wendler, O; Vivian, G
Abstract : Introduction: Perioperative mortality of patients who undergo heart valve surgery for carcinoid heart valve disease has been observed to be high (5%–10%). We investigated whether peptide receptor radiotherapy with lutetium-177 dotatate can be used safely in patients with neuroendocrine neoplasm carcinoid heart valve disease and if there is associated survival advantage by reducing overall exposure of the valves to high doses of vasoactive peptides. Method: Retrospective case notes review was performed on 18 neuroendocrine neoplasm patients (mean 60 years), who underwent heart valve surgery between 2003 and 2017 for carcinoid heart valve disease, 9 of whom received peptide receptor radiotherapy in addition to surgery. Results: All patients were treated with somatostatin receptor antagonists and underwent cardiac valvular surgery (mean two valves replaced) and three benefitted from additional coronary bypass grafting. Nine patients underwent surgery alone: in this group, the time from surgery to progression was 14 months (mean; SD 13.5 months). Nine were treated with peptide receptor radiotherapy in addition to surgery. Six underwent surgery with peptide receptor radiotherapy on progression. Time to progression from surgery to first peptide receptor radiotherapy was mean 25.1 months (SD 23.6 months). No patients developed peritreatment cardiac complications. There were no deaths within the 30-day postoperative period. Average time from surgery to last follow-up/death was 41 months (6–79) in the surgery + lutetium group and in the surgery only group 17 months (1–24). Nine patients died, five in the surgery + lutetium group and four in the surgery only group, all at greater than 1-year postsurgery. Discussion: Peptide receptor radiotherapy is safe in the setting of Carcinoid valvular heart disease in patients with controlled heart failure, PPRT can be use in the pre- and post-valve surgery period. There appears to be a survival benefit of having peptide receptor radiotherapy. Further evidence for peptide receptor radiotherapy in the neoadjuvant setting prior to cardiothoracic surgery is required.